2021
DOI: 10.3748/wjg.v27.i24.3466
|View full text |Cite
|
Sign up to set email alerts
|

Non-cirrhotic hepatocellular carcinoma in chronic viral hepatitis: Current insights and advancements

Abstract: Primary liver cancers carry significant morbidity and mortality. Hepatocellular carcinoma (HCC) develops within the hepatic parenchyma and is the most common malignancy originating from the liver. Although 80% of HCCs develop within background cirrhosis, 20% may arise in a non-cirrhotic milieu and are referred to non-cirrhotic-HCC (NCHCC). NCHCC is often diagnosed late due to lack of surveillance. In addition, the rising prevalence of non-alcoholic fatty liver disease and diabetes mellitus have increased the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 119 publications
(134 reference statements)
2
10
0
Order By: Relevance
“…In our study, the prevalence of cirrhotic patients was slightly higher than that expected from the literature data (about 80% [23]), but compatible with a cohort in which HCV is still the main cause [24], despite a progressive increase in NAFLD as a cause (or a contributing cause) of HCC (from 17% to about 40%). This figure reflects the prediction that NAFLD will be the leading cause of HCC over the next decade [25], but it appears to have even worsened perhaps due to social restrictions and home confinement that limited physical activity; furthermore, we may have been more sensitive to reporting NAFLD as a contributing cause: in fact, its increase is not proportional to the decrease in viral infection, but is added to them.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the prevalence of cirrhotic patients was slightly higher than that expected from the literature data (about 80% [23]), but compatible with a cohort in which HCV is still the main cause [24], despite a progressive increase in NAFLD as a cause (or a contributing cause) of HCC (from 17% to about 40%). This figure reflects the prediction that NAFLD will be the leading cause of HCC over the next decade [25], but it appears to have even worsened perhaps due to social restrictions and home confinement that limited physical activity; furthermore, we may have been more sensitive to reporting NAFLD as a contributing cause: in fact, its increase is not proportional to the decrease in viral infection, but is added to them.…”
Section: Discussionsupporting
confidence: 87%
“…As a result, improper medication withdrawal may result in disease progression. We also speculated whether long-term untreated OBI with positive HBeAg would more likely to result in the occurrence of adverse consequences such as liver cirrhosis and HCC, which has been reported in OBI with HBeAg negativity ( Perisetti et al, 2021 ; Huang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, one year after treatment, the patient was incidentally found to have a liver lesion consistent with HCC. Classically, HCC occurs in the setting of cirrhosis, but up to 20% of cases occur in non-cirrhotics, most often associated with chronic viral hepatitis (B/C), nonalcoholic fatty liver disease, hemochromatosis, alpha-1 antitrypsin deficiency, aflatoxin exposure, or other toxin exposure [ 8 ]. The incidence of HCC in non-cirrhotic patients with HCV ranges from 4.4%-10.6% [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of HCC in non-cirrhotic patients with HCV ranges from 4.4%-10.6% [ 9 ]. Studies have shown that HCC risk is still increased after HCV eradication [ 8 ], implying a direct oncogenic effect of the virus. HCV viral proteins have been shown to inhibit tumor suppressor genes and cell cycle checkpoints, causing the increased cell growth and division seen in cancer [ 10 ].…”
Section: Discussionmentioning
confidence: 99%